Sustaining port competitive advantage: An application of resource-based view approach - Arbak, Salwani; Nik Abdullah, Nik Ab. Halim (2013)
This research aims to determine the relationship of port resources and capabilities with the port performance. The data was collected through self-administered survey and mail questionnaires.The results from the findings indicate that port tangible resources such as financial assets, technology assets and physical assets are playing a significant role to increase performance of Malaysian port.Meanwhile, for port intangible assets such as intellectual property assets, organizational assets and capabilities, the study found that these resources have significantly contributed to the higher port performance as compared to port tangible assets.Most interestingly, the findings also discover that the organizational assets such as port culture, structure of the firms, firm human resource policies, port contract in the vertical and horizontal integration and port reputation show the highest significant level as compared to other components in the port intangible assets.This study extends the body of literature related to the source of port competitive advantage. The findings of this research are also providing important contributions for practitioners and policy makers in developing policies and strategies for promoting Malaysia as a world maritime nation.